Analysis Of Clean Water Availability On Household Environmental Health - Glory Gelarich Simanjuntak; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Clean water is crucial​ component in maintaining a healthy household Adequate environment​ availability of clean water can support good hygiene and sanitation practices and prevent various environmental diseases. This study aims to analyze the relationship between clean water availability and household environmental health. The study used an analytical design with a cross-sectional approach. The study sample consisted of 80 households selected using a purposive sampling technique. Data were collected through observation and interviews using a structured questionnaire. Data analysis used the chi-square test. The results showed that households with good clean water availability had better environmental health conditions than households with inadequate clean water availability. The statistics test results showed a p- value of 0.018 (p < 0.05). It was concluded that there is a significant relationship between clean water availability and household environmental health.